2007
DOI: 10.1128/mcb.01780-06
|View full text |Cite
|
Sign up to set email alerts
|

Wilms' Tumor Protein Wt1 Is an Activator of the Anti-Müllerian Hormone Receptor Gene Amhr2

Abstract: The Wilms' tumor protein Wt1 plays an essential role in mammalian urogenital development. WT1 mutations in humans lead to a variety of disorders, including Wilms' tumor, a pediatric kidney cancer, as well as Frasier and Denys-Drash syndromes. Phenotypic anomalies in Denys-Drash syndrome include pseudohermaphroditism and sex reversal in extreme cases. We have used cDNA microarray analyses on Wt1 knockout mice to identify Wt1-dependent genes involved in sexual development. The gene most dramatically affected by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 62 publications
(61 reference statements)
2
50
0
Order By: Relevance
“…E, the Wt1(ϩKTS) isoform, which lacks 3 amino acids in its zinc finger domain (36), did not bind to the oligonucleotides (lanes 3, 6, and 9). ducts, are among the genes that are regulated by Wt1 (41,52,53). Consistently, male-to-female sex reversal or genital tract abnormalities were observed in XY patients with heterozygous Wt1 germ line mutations (54), underscoring the role of Wt1 in testis determination.…”
Section: Wt1 Regulates Adamts16 In Developing Kidneys and Gonadsmentioning
confidence: 66%
“…E, the Wt1(ϩKTS) isoform, which lacks 3 amino acids in its zinc finger domain (36), did not bind to the oligonucleotides (lanes 3, 6, and 9). ducts, are among the genes that are regulated by Wt1 (41,52,53). Consistently, male-to-female sex reversal or genital tract abnormalities were observed in XY patients with heterozygous Wt1 germ line mutations (54), underscoring the role of Wt1 in testis determination.…”
Section: Wt1 Regulates Adamts16 In Developing Kidneys and Gonadsmentioning
confidence: 66%
“…S8). Interestingly, we observed that amhr2, the receptor of amh (Wu et al 2010), and wt1a and wt1b, potential activators of amhr2 (Klattig et al 2007), also showed differential methylation between ZW/ZZ testes and ovaries (Supplemental Fig. S8).…”
Section: Genomic Methylation Patterns Are Consistent With Gonadal Difmentioning
confidence: 94%
“…8B). Others have reported that the Amhr2 promoter is also regulated by NR5A1 and WT1 (Teixeira et al 1999, Hossain & Saunders 2003, Klattig et al 2007). Interestingly, we have shown these two factors synergize with GATA4 on multiple gonadal promoters including Sry, Cyp19a1, HSD3B2, and Inha (Tremblay & Viger 2001, Bouchard et al 2005, Martin et al 2005, Miyamoto et al 2008.…”
Section: Discussionmentioning
confidence: 99%